2016
DOI: 10.1021/acs.jafc.6b04468
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Anti-obesity Effects and Different Mechanisms of Action

Abstract: Obesity, a primary influence on health condition, causes numerous comorbidities and complications and, therefore, pharmacotherapy is considered a strategy for its treatment. However, the adverse effects of most chemical drugs targeting weight loss complicate their approval by regulatory authorities. Recently, interest has increased in the development of ingredients from natural sources with fewer adverse effects for preventing and ameliorating obesity. This review provides an overview of current anti-obesity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(110 citation statements)
references
References 167 publications
1
109
0
Order By: Relevance
“…The inhibition of nutrient digestion and absorption is one of the effective strategies to prevent obesity and type 2 diabetes. In previous studies, inhibition of the activity of pancreatic lipase, α-glucosidase, and α-amylase, which are involved in dietary carbohydrate and lipid degradation, has been found to be positively correlated with reduced fat and sugar absorption from the gastrointestinal tract (Fu, Jiang, Guo, & Su, 2016;Kumar, Narwal, Kumar, & Prakash, 2011;Sales, Souza, Simeoni, Magalhães, & Silveira, 2012). It has been reported that modest coffee intake can slow down diabetes.…”
mentioning
confidence: 98%
“…The inhibition of nutrient digestion and absorption is one of the effective strategies to prevent obesity and type 2 diabetes. In previous studies, inhibition of the activity of pancreatic lipase, α-glucosidase, and α-amylase, which are involved in dietary carbohydrate and lipid degradation, has been found to be positively correlated with reduced fat and sugar absorption from the gastrointestinal tract (Fu, Jiang, Guo, & Su, 2016;Kumar, Narwal, Kumar, & Prakash, 2011;Sales, Souza, Simeoni, Magalhães, & Silveira, 2012). It has been reported that modest coffee intake can slow down diabetes.…”
mentioning
confidence: 98%
“…A purified extract of Hoodia, known as P57, was injected in an in vivo study directly into the brains of rats and easily broken down by the liver (Spadafranca et al 2013). However, an in vitro study was found that P57 was generally not inhibited metabolically by human liver enzymes and has a relatively high secretion rate (Fu et al 2016).…”
Section: Appetite Suppressantsmentioning
confidence: 99%
“…7 Phytochemicals are one of the possible ways to regulate the energy metabolism and lower the risks of developing obesityrelated complications. [8][9][10] To date, studies have reported several plants with substances that can inhibit adipogenesis with different action mechanisms. In this context, Artemisia species have produced different results in terms of their effects on adipogenesis.…”
Section: Introductionmentioning
confidence: 99%